Intake of NFE, Crude Fibre and Extract Eter of Male Kacang Goats in the Realimentation Phase after Experiencing Different Levels of Feed Restriction - Tahuk, Paulus Klau; Bira, Gerson Frans; Luruk, Bernadina (Journal of Tropical Animal Science and Technology, 2024)
This study aims to determine the intake of nitrogen free extract (NFE), crude fiber (CF), and extract eter (EE) of male Kacang goats in the realimentation phase after experiencing different levels of feed restriction. This study used the experimental method Completely Randomized Design (CRD) which consisted of 3 treatments and 5 replications that is T0 livestock without feed restrictions, T1: livestock are limited to 100% of basic life, T2: livestock are limited to 50% of basic life. Variables observed included NFE, crude fiber, and crude fat intake. The results showed that the NFE, CF and EE of male kacang goats in the realimentation phase of the 3 group were not different/ or significant (P > 0.05). The intake of NFE each treatment is a T0 treatment 222,63±18,17; T1 210,12±29,79, and T2 186,72±34,89. The intake of CF (g/e/h) in treatment T0 56,32±2,47; T1 51,94±9,20; and T2 was 49,82±8,79. The intake of EE (g/e/h) in treatment T0 treatment of 10,19±1,10; T1 9,68±1,37; and T2 8,41±1,64. It can be concluded that the intake of NFE, CF and EE in the realimentation phase of livestock restricted feed 100% according to basic life and 50% below the main life is not much different from the Kacang goats which are given normal feed according to their needs.